Education Development for Rohingya Muslims in Bangladesh: Contributions of Local and International Organizations - Hoque, Md. Ziaul (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2025)
Despite residing in Myanmar since the eighth century, Rohingya Muslims were rendered stateless under the 1982 Burmese Citizenship Law, leading to systemic exclusion and large-scale displacement. Today, over one million Rohingya refugees live in Bangladesh, where education remains a critical and underdeveloped area of response. This study provides a holistic analysis of the educational crisis facing Rohingya children, emphasizing the historical, legal, and social barriers to access, and evaluating the role of local and international organizations in addressing these challenges. Employing a qualitative research design, the study combines historical analysis, document reviews, and thematic analysis with insights from 12 semi-structured interviews involving NGO representatives, educators, and local authorities. Secondary quantitative data from Cox’s Bazar Education Sector supported trend interpretation. Findings reveal that initiatives such as the Learning Competency Framework and Approach (LCFA) and the Myanmar Curriculum Pilot Programme have expanded access for over 300,000 children across 3,400 learning centers. However, ongoing issues include a lack of formal certification, high dropout rates, teacher shortages, sociocultural restrictions, and declining enrollment. This research contributes a layered understanding of the Rohingya education crisis by integrating historical context with field-based evidence. It offers evidence-based recommendations to support formal curriculum recognition, expand long-term funding, enhance teacher training, particularly for women, and integrate psychosocial support and community-led models. The findings aim to inform policy, advocacy, and sustainable planning in refugee education across protracted crisis contexts.